Hierarchical division-based cache storage strategy in content-centric networking - Jun LI; ming FENGZong; bo WUHai; Jiang ZHI (Tongxin xuebao)
For the issue of improving the performance of in-network cache in content-centric networking, a hierarchical division-based lightweight collaboration cache storage strategy was proposed. According to the strategy, content was grouped into different hierarchies by the cooperation Interest package, Data package and the local PIT of routers, so that the contents could be cached in different nodes along the delivery path. The performance of the scheme was eva-luated by comparing with the well-known schemes through simulation. Experimental results indicate that the scheme has good performance in reducing access hops, increasing the average cache hit ratio and reducing the server load.